Rereading Frankenstein: What If Victor Frankenstein Had Actually Been Evil? - Robert, Jason Scott (Hastings Center Report, 2018)
As we reread Mary Shelley's Frankenstein at two hundred years, it is evident that Victor Frankenstein is both a mad scientist (fevered, obsessive) and a bad scientist (secretive, hubristic, irresponsible). He's also not a very nice person. He's a narcissist, a liar, and a bad "parent." But he is not genuinely evil. And yet when we reimagine him as evil—as an evil scientist and as an evil person—we can learn some important lessons about science and technology, our contemporary society, and ourselves.